Design and assessment of myoelectric games for prosthesis training of upper limb amputees - MEERALAKSHMI RADHAKRISHNAN (Institutional Knowledge at Singapore Management University, 2019)
In this paper, we present the design and evaluation of our system, which provides an engaging game-based pre-prosthesis training environment for upper limb transradial amputees. We believe that patients who train using such a training tool will demonstrate significantly higher improvement in functional performance tests using a myoelectric prosthesis than when conventional pre-prosthesis training protocols are used. We re-designed two simple games to be playable using three muscle contractions which are appropriate to pre-prosthesis exercises and are detected by an EMG-based arm sleeve. Through user studies conducted with 16 non-amputee subjects, we show that the proposed games are enjoyable, fun to play, sustains motivation to continue playing and also helps in improving muscular control. Using an HMM trained on EMG data collected from the game play sessions of each user, we are able to detect if the subject felt fatigued, while continuously contracting the muscles to play the game, in 93% of the cases and with a latency of only ±15 seconds. We are also able to understand the subject's quality of muscle isolation during the game play.